2015
DOI: 10.1002/aelm.201400026
|View full text |Cite
|
Sign up to set email alerts
|

pn‐Heterojunction Diodes with n‐Type In2O3

Abstract: contact metals, diodes with rectifi cation suffi cient for material characterization were reported. [ 33 ] Nevertheless, rectifi cation has to be improved considerably to exploit In 2 O 3 within detectors or transistors. The realization of pn-heterodiodes is an alternative approach toward rectifying devices and was successful for the case of ZnO as n-type layer as mentioned above. As recently demonstrated, ZnCo 2 O 4 and NiO are especially interesting as p-type layer since they can be deposited at room tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 39 publications
(78 reference statements)
1
25
0
Order By: Relevance
“…Since the first all‐oxide junction diode demonstrated by Kudo et al, an increasing number of studies have been reported, with very good results . In spite of the short research history on oxide‐based p–n junctions, excellent‐performance devices were reported on p‐type amorphous ZnO·Rh 2 O 3 and ZnCo 2 O 4 (ZCO) . For a ZCO‐based diode, a recent report showed a large forward current to reverse current ( I f / I r ) ratio of ca.…”
Section: Performance Of Oxide‐based P–n Junctionsmentioning
confidence: 91%
See 1 more Smart Citation
“…Since the first all‐oxide junction diode demonstrated by Kudo et al, an increasing number of studies have been reported, with very good results . In spite of the short research history on oxide‐based p–n junctions, excellent‐performance devices were reported on p‐type amorphous ZnO·Rh 2 O 3 and ZnCo 2 O 4 (ZCO) . For a ZCO‐based diode, a recent report showed a large forward current to reverse current ( I f / I r ) ratio of ca.…”
Section: Performance Of Oxide‐based P–n Junctionsmentioning
confidence: 91%
“…In 2010, Kim et al fabricated p‐type ZnCo 2 O 4 thin film and the related p–n‐junction diode by PLD with controllable electrical performance, showing a bandgap of 2.3 eV and a conductivity of 21 S cm −1 , while the carrier density could be tuned from 10 16 to 10 20 cm −3 by controlling the oxygen pressure . Recently, Grundmann and co‐workers demonstrated high‐performance amorphous p–n‐junction diodes and junction field‐effect transistors using p‐type spinel oxide ZnCo 2 O 4 deposited at room temperature, indicating the great potential of this material, despite its low hole mobility (<0.1 cm 2 V −1 s −1 ) …”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidesmentioning
confidence: 99%
“…Besides high power applications, Ga 2 O 3 and its alloys are suited for solar‐blind photo detection, realized so far by Schottky barrier metal‐semiconductor‐metal structures . However, heterojunction diodes comprising group‐III sesquioxides were also reported in terms of NiO/Ga 2 O 3 , Cu 2 O/Ga 2 O 3 , NiO/In 2 O 3 , and ZnCo 2 O 4 /In 2 O 3 pn‐heterostructures . In case of NiO/Ga 2 O 3 , the p‐type layer was Li‐doped and grown by the sol‐gel method on (100) β ‐Ga 2 O 3 single crystals with a free electron concentration of 5 × 10 17 cm −3 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Secondly, as a p-type transparent semiconductor it is a very relevant material for oxide-based gas sensors 8,9 as well as for pn-diodes and other transparent oxide electronics. 1,10,11 Additionally, NiO can be used as a hole transport and electron blocking layer in organic solar cells. 12 NiO films have already been grown by many methods, including sputtering, [13][14][15] metal evaporation with oxygen or nitrogen dioxide inlet, 16 pulsed laser deposition (PLD), 3,17 sol-gel coating, 18 or plasma-assisted molecular beam epitaxy (PA-MBE).…”
Section: Introductionmentioning
confidence: 99%